The growth response of coffee (Coffea arabicaÂ L) plants to organic manure, inorganic fertilizers and integrated soil fertility management under different irrigation water supply levels - Abel Chemura (International Journal of Recycling of Organic Waste in Agriculture)
A study was carried out to determine the effects of organic, inorganic fertilizers and integrated soil fertility management and irrigation levels (1,000, 750 and 500 ml per planting station) on coffee growth. There were no significant differences (p[0.05) in girth, number of leaves and number of primaries due to the different soil fertility management options. Significant differences (p.05) due to soil nutrient sources were observed in coffee height where inorganic fertilizer treatment resulted in tallest coffee plants (47.4 cm) and integrated soil fertility having the shortest coffee trees (42.8 cm) after 1 year. The highest irrigation level of 1,000 ml had the tallest plants with thickest stems while the lowest level had the shortest and thinnest plants (p.05). No significant differences were observed in the number of leaves and number of primaries due to irrigation treatments. Results indicate that inorganic fertilizers are the most effective at high irrigation levels while organic manure performs better than inorganic fertilizers under low irrigation water levels.